The abundance of soil bacteria applied with compost and Trichoderma sp. in tangerine orchard - Edi Siswadi; Nantil Bambang Eko Sulistyono; Refa Firgiyanto; Gallyndra Fatkhu Dinata; Hanif Fatur Rohman; Fadil Rohman (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
.